2020
DOI: 10.1002/cnma.202000269
|View full text |Cite
|
Sign up to set email alerts
|

Oxidative Originators of Graphene Barrier Coating Grown on Surfaces

Abstract: Graphene coating has been proposed to be a promising oxidation barrier for metals because of its chemical inertia and physical impermeability. Nevertheless, chemical vapor deposition (CVD)‐grown graphene on metal surfaces results in many structural defects and growth imperfections, which would serve as oxidative originators and favor a substantial galvanic corrosion at such interfaces in the long term. On this basis, oxidative originators including graphene structural defects and CVD growth imperfections of gr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 117 publications
0
3
0
Order By: Relevance
“…It has a promising development in the field of metal anticorrosion due to its good performance in impermeability to small molecules with large aspect ratio and excellent chemical stability. It was found that graphene coating with double or triple layers generated by chemical vapor sediment (CVD) can offer great inhibition against corrosion to copper substrate in air or in 0.1 mol L −1 NaCl solution [1][2][3][4][5][6][7][8][9]. On the contrary, the monolayer and multilayer graphene has more defects, of which the corrosion resistance is reduced.…”
Section: Introductionmentioning
confidence: 99%
“…It has a promising development in the field of metal anticorrosion due to its good performance in impermeability to small molecules with large aspect ratio and excellent chemical stability. It was found that graphene coating with double or triple layers generated by chemical vapor sediment (CVD) can offer great inhibition against corrosion to copper substrate in air or in 0.1 mol L −1 NaCl solution [1][2][3][4][5][6][7][8][9]. On the contrary, the monolayer and multilayer graphene has more defects, of which the corrosion resistance is reduced.…”
Section: Introductionmentioning
confidence: 99%
“…Graphene is a typical two-dimensional (2D) material with a tight hexagonal structure and many kinds of outstanding properties such as high strength, excellent thermal conductivity, and superior impermeability to gases [1][2][3][4]. These properties make graphene an excellent corrosion barrier for metals, because it acts as a good physical barrier, being chemically inert, preventing metals from coming into contact with O 2 and H 2 O in the surroundings [5][6][7][8][9]. However, it has been revealed that the graphene coating provides corrosion protection for the metal only for a short period of time.…”
Section: Introductionmentioning
confidence: 99%
“…In principle, the dense hexagonal honeycomb structure of perfect graphene lattice would isolate the metals from any corrosive elements [8][9][10]. However, the structural defects and growth imperfections in graphene are inevitably created accompanying the CVD processes and facilitate the mass transport of corrosive species as a pathway [11]. Recently, many graphene defects such as grain boundaries, vacancies, wrinkles, and the incommensurate coupling of graphene-Cu system [12][13][14][15][16][17] have been revealed to cause oxidative damages correlated with a galvanic corrosion in the long term [18,19].…”
Section: Introductionmentioning
confidence: 99%